2003
DOI: 10.1111/j.0014-3820.2003.tb00288.x
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific Competition and Mating Between Fungal Strains of the Anther Smut Microbotryum Violaceum From the Host Plants Silene Latifolia and S. Dioica

Abstract: Abstract. We studied intraspecific competition and assortative mating between strains of the anther smut fungus Microbotryum violaceum from two of its host species, Silene latifolia and S. dioica. Specifically, we investigated whether strains from allopatric host populations have higher competitive ability on their native host species and show positive assortative mating. In general, strains isolated from S. latifolia outcompeted strains isolated from S. dioica on both host species, but in female hosts, hetero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 45 publications
3
14
1
Order By: Relevance
“…EM taxa deserve more studies combining intersterility tests and evaluation of gene flow by tools of population genetics between potential trans-or inter-continental CBSs. In particular, it is unclear whether dikaryons produced by mating between allopatric haploids are more or less fit than those issuing from mating between sympatric haploids: this question, which is central to gene flow in nature, has received conflicting answers for fungal pathogens (Van Putten et al 2003;James et al 2008) and can be expected to vary among species complexes. Lastly, the distinction between allo-and sympatric CBSs is not always straightforward: Geml et al (2006) found three geographic clades within A. muscaria sensu lato that coexist (perhaps secondarily) in parapatry in Northern America (Geml et al 2009); European CBSs detected in T. scalpturatum complex are also sympatric (Carriconde et al 2008a, 2008b, Jargeat et al 2010.…”
Section: Cryptic Biological Species (Cbss)mentioning
confidence: 99%
“…EM taxa deserve more studies combining intersterility tests and evaluation of gene flow by tools of population genetics between potential trans-or inter-continental CBSs. In particular, it is unclear whether dikaryons produced by mating between allopatric haploids are more or less fit than those issuing from mating between sympatric haploids: this question, which is central to gene flow in nature, has received conflicting answers for fungal pathogens (Van Putten et al 2003;James et al 2008) and can be expected to vary among species complexes. Lastly, the distinction between allo-and sympatric CBSs is not always straightforward: Geml et al (2006) found three geographic clades within A. muscaria sensu lato that coexist (perhaps secondarily) in parapatry in Northern America (Geml et al 2009); European CBSs detected in T. scalpturatum complex are also sympatric (Carriconde et al 2008a, 2008b, Jargeat et al 2010.…”
Section: Cryptic Biological Species (Cbss)mentioning
confidence: 99%
“…Generally, most Microbotryum species have high selfing rates [24], thus limiting the probability of interspecific gene flow [26-28]. Mechanisms of pre-mating barriers in the form of assortative mating have been investigated but not found [29,30]. When hybridization is achieved experimentally, it often leads to the production of unbalanced meiotic products with limited growth and reduced infection ability [30].…”
Section: Introductionmentioning
confidence: 99%
“…The M. violaceum–S. latifolia system is an important biological model for the study of host–parasite evolution [8,1518]. The fungus sterilizes the hosts by destroying ovaries and replacing pollen with fungal spores that are then dispersed by natural pollinators of the plant (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…latifolia after experimental inoculation by several genotypes of M. violaceum [18,19] and in experimental populations [20], with different fungal genotypes segregating in different stems of the plant. Even more interestingly, experimental inoculations showed that sequential inoculations with more related genotypes led to a higher frequency of multiple infections than sequential inoculation with less related genotypes even though the different strains inoculated alone yielded similar levels of infection [8].…”
Section: Introductionmentioning
confidence: 99%